The Role of Intestinal Microbial Metabolites in the Immunity of Equine Animals Infected With Horse Botflies - Hu, Dini; Tang, Yujun; Wang, Chen; Qi, Yingjie; Ente, Make; Li, Xuefeng; Zhang, Dong; Li, Kai; Chu, Hongjun (Frontiers in Veterinary Science, 2022)
The microbiota and its metabolites play an important role in regulating the host metabolism and immunity. However, the underlying mechanism is still not well studied. Thus, we conducted the LC-MS/MS analysis and RNA-seq analysis on Equus przewalskii with and without horse botfly infestation to determine the metabolites produced by intestinal microbiota in feces and differentially expressed genes (DEGs) related to the immune response in blood and attempted to link them together. The results showed that parasite infection could change the composition of microbial metabolites. These identified metabolites could be divided into six categories, including compounds with biological roles, bioactive peptides, endocrine-disrupting compounds, pesticides, phytochemical compounds, and lipids. The three pathways involving most metabolites were lipid metabolism, amino acid metabolism, and biosynthesis of other secondary metabolites. The significant differences between the host with and without parasites were shown in 31 metabolites with known functions, which were related to physiological activities of the host. For the gene analysis, we found that parasite infection could alarm the host immune response. The gene of “cathepsin W” involved in innate and adaptive immune responses was upregulated. The two genes of the following functions were downregulated: “protein S100-A8” and “protein S100-A9-like isoform X2” involved in chemokine and cytokine production, the toll-like receptor signaling pathway, and immune and inflammatory responses. GO and KEGG analyses showed that immune-related functions of defense response and Th17 cell differentiation had significant differences between the host with and without parasites, respectively. Last, the relationship between metabolites and genes was determined in this study. The purine metabolism and pyrimidine metabolism contained the most altered metabolites and DEGs, which mainly influenced the conversion of ATP, ADP, AMP, GTP, GMP, GDP, UTP, UDP, UMP, dTTP, dTDP, dTMP, and RNA. Thus, it could be concluded that parasitic infection can change the intestinal microbial metabolic activity and enhance immune response of the host through the pathway of purine and pyrimidine metabolism. This results will be a valuable contribution to understanding the bidirectional association of the parasite, intestinal microbiota, and host.